Integrating emotional and spiritual quotient into the P5 program for bullying prevention in elementary schools - Agus Hasan Saputra; Andewi Suhartini (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2025)
Bullying continues to be a serious problem in education, eroding children’s emotional health, pulling down their academic motivation, and distorting the positive atmosphere in their classrooms. Deepening character education by weaving together the Pancasila Student Profile (P5) values and the Emotional-Spiritual Quotient (ESQ) framework helps students master self-control and cultivates a culture of respect to prevent bullying. This study aimed to examine the implementation of the Pancasila Student Profile Strengthening (P5) theme ‘Building Soul and Body’ by integrating the Emotional and Spiritual Quotient (ESQ) approach as a strategy for bullying prevention in elementary schools. Conducted at SDN 224 Cijambe, Bandung, the research adopted a Classroom Action Research (CAR) design involving 84 fourth-grade students over two weeks. The study integrated lectures, group discussions, simulations, and reflective activities to foster empathy, emotional regulation, and social skills. The findings reveal that bullying behaviors, such as verbal teasing, significantly decreased from 40% to 10%, while active participation in group activities increased from 20% to 75%. Students demonstrate a deeper awareness of respecting their peers, fostering a more positive classroom environment. Activities such as collaborative games and discussions allowed students to reflect on their actions and develop emotional intelligence. This research highlights the success of integrating P5 and ESQ in character education, emphasizing the importance of empathy, responsibility, and social harmony in combating bullying. Teachers played a pivotal role as facilitators and role models in program success, though challenges such as time constraints in implementation were noted. This approach offers a scalable model for broader application in other educational settings.Keywords: Bullying prevention, character development, elementary education, ESQ